Play-Based Emotional Training and Engagement for Normalizing Distress (Pretend) in Preschool Children at Provincial General Hospital of North Sulawesi - Molintao, Winarsi Pricilya; Legi, Julita Roslia; Baithesda (NUTRIX, 2026)
Hospitalization can trigger emotional distress in preschool children due to separation, unfamiliar surroundings, and invasive procedures. This study aimed to determine the effectiveness of Play-Based Emotional Training and Engagement for Normalizing Distress (PRETEND) in reducing emotional distress. A quasi-experimental design with a pretest-posttest control group involved 44 children aged 3–5 years at the North Sulawesi Provincial Hospital (2025), divided into intervention (n=22) and control (n=22) groups. Distress was measured using the OSBD-R, as well as questionnaires on child involvement, parental satisfaction, and perceived benefits. The results showed a significant decrease in distress scores in the intervention group from 6.77 ± 1.27 to 0.45 ± 0.67, while the control group remained high (5.36 ± 1.56). Child involvement was classified as moderate–high, parental satisfaction was very high, and program perceptions were very positive. It was concluded that PRETEND was effective in reducing emotional distress and increasing parental involvement and satisfaction. This intervention is recommended as part of child closure practice, with further research to assess long-term effects. Hospitalisasi dapat memicu distress emosional pada anak pra-sekolah akibat perpisahan, lingkungan asing, dan tindakan invasif. Penelitian ini bertujuan mengevaluasi efektivitas Play-Based Emotional Training and Engagement for Normalizing Distress (PRETEND) dalam menurunkan distress emosional. Desain quasi-eksperimen dengan pretest-posttest kelompok kontrol melibatkan 44 anak usia 3–5 tahun di RSUD Provinsi Sulawesi Utara (2025), yang dibagi menjadi kelompok intervensi (n=22) dan kontrol (n=22). Distress diukur menggunakan OSBD-R, serta kuesioner keterlibatan anak, kepuasan orang tua, dan persepsi manfaat. Hasil menunjukkan penurunan signifikan skor distress pada kelompok intervensi dari 6,77 ± 1,27 menjadi 0,45 ± 0,67, sementara kelompok kontrol tetap tinggi (5,36 ± 1,56). Keterlibatan anak tergolong sedang–tinggi, kepuasan orang tua sangat tinggi, dan persepsi program sangat positif. Disimpulkan bahwa PRETEND efektif menurunkan distress emosional dan meningkatkan keterlibatan serta kepuasan orang tua. Intervensi ini direkomendasikan sebagai bagian praktik keperawatan anak, dengan penelitian lanjutan untuk menilai efek jangka panjang.